A History of Displaced Knowledge : Austrian Refugees from National Socialism in Australia - Strobl, Philipp (Brill, 2025)
The book examines the migration of ideas and knowledge carried in the cultural baggage of Austrian refugees who fled to Australia in 1938 and 1939 to escape National Socialism. Through 26 life stories, it explores the processes of acquisition, transmission, translation, and adaptation of cultural capital, as well as its long-term impact on the host society. The study highlights the diverse strategies refugees employed to first escape their homeland and later negotiate and apply their knowledge in Australia. Das Buch untersucht die Migration von Ideen und Wissen im kulturellen Gepäck österreichischer Flüchtlinge, die 1938 und 1939 vor dem Nationalsozialismus nach Australien flohen. Anhand von 26 Lebensgeschichten zeigt es die Prozesse der Aneignung, Übertragung, Übersetzung und Anpassung kulturellen Kapitals sowie dessen langfristige Auswirkungen auf die Aufnahmegesellschaft auf. Dabei wird deutlich, dass die Flüchtlinge unterschiedliche Strategien nutzten, um zunächst ihrer Heimat zu entkommen und später ihr Wissen in Australien zu verhandeln und anzuwenden.